Six Useful Websites for Practitioners Working in Schools - VanDerwall, Rena (Behav Anal Pract, 2020)
A substantial, and seemingly increasing, number of Board Certified Behavior Analysts work in pre-K–12 schools. Many of them will be unfamiliar with the roles and activities of other school professionals, as well as with the structure, function, and mandates of schools. This article introduces 6 websites that are devoted to education. Accessing these free and user-friendly sites can provide practitioners with information and training activities that will help them function comfortably and competently in schools and benefit their clients to a greater extent. Our purpose in writing this article is to introduce and recommend these websites.